2014
DOI: 10.4236/ojapo.2014.33006
|View full text |Cite
|
Sign up to set email alerts
|

Clomiphene Citrate Induces ROS-Mediated Apoptosis in Mammalian Oocytes

Abstract: The clomiphene citrate (CC), a nonsteroidal triphenylethylene compound, is a first line of medicine used for the induction of ovulation in anovulatory women worldwide. In spite of high ovulation induction with the use of CC, the pregnancy rate is much lower. Such a discrepancy could be due to the peripheral anti-estrogenic effect of CC, particularly at the level of ovary, endometrium and cervical mucus. CC induces ovulation by binding to the estrogen receptors and generates hypoestrogrnic state in hypothalamus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…This concept is further enhanced by investigations that have shown OS induced apoptosis in granulosa cells resulting in the reduction of estradiol levels and atresia of follicles . Chaube et al ., showed that OS disrupts granulosa cells‐oocyte communication resulting in decreased quality of oocytes . This notion is further supported by the observations that the OS caused chromosomal segregation disorders, shortening of telomere, oocyte fragmentation and fertilization failures .…”
Section: Introductionmentioning
confidence: 52%
“…This concept is further enhanced by investigations that have shown OS induced apoptosis in granulosa cells resulting in the reduction of estradiol levels and atresia of follicles . Chaube et al ., showed that OS disrupts granulosa cells‐oocyte communication resulting in decreased quality of oocytes . This notion is further supported by the observations that the OS caused chromosomal segregation disorders, shortening of telomere, oocyte fragmentation and fertilization failures .…”
Section: Introductionmentioning
confidence: 52%
“…The increased cytochrome c activates upstream and downstream caspases in mouse oocytes (Liu et al, ; Zhang and Fissore, ). The caspase‐3 disrupt the histoarchitecture of oocyte by disrupting the structural and regulatory proteins, which results several biochemical and morphological changes during oocyte apoptosis (Chaube et al, , ,; Tripathi et al, , , ; Tiwari et al, , ; Zhu et al, ) (Fig. ).…”
Section: Role Of Ca++ In Meiotic Resumption From Diplotene Arrestmentioning
confidence: 99%
“…It is generally accepted that ROS act as signal molecules in a wide variety of cells, including germ cells in mammals . A moderate increase of ROS is beneficial for meiotic cell cycle progression in vitro , while high levels of ROS induce cell cycle arrest and apoptosis . Generation of ROS is associated with a reduced level of 3′,5′‐cyclic adenosine monophosphate (cAMP) as well as 3′,5′‐cyclic guanosine monophosphate (cGMP) levels during spontaneous meiotic resumption from diplotene arrest in rat oocytes cultured in vitro .…”
Section: Introductionmentioning
confidence: 99%